Comparative Evaluation of Polysaccharide Binders on the Quality Characteristics of Plant-Based Patties - Jong-Hyeon Han; Dong-Hyun Keum; Seong-Joon Hong; Yea-Ji Kim; Sung-Gu Han (Foods, 2023)
Polysaccharides have been used in the production of plant-based meat analogs to replicate the texture of real meat. However, there has been no study that comprehensively compares the effects of different polysaccharides, and a limited number of polysaccharides have been evaluated. Thus, we aimed to identify the most suitable polysaccharide and concentration for plant-based patties. Plant-based patties were manufactured by blending different concentrations (0%, 1%, and 2%) of six polysaccharides with other ingredients, and the quality characteristics and sensory properties were evaluated. The L* values of plant-based patties reduced during the cooking process resembled the color change of beef patty (BP). In particular, a 2% κ-carrageenan-added patty (Car-2) exhibited the lowest L* value among the plant-based patties, measured at 44.05 (p < 0.05). Texture parameters exhibited high values by adding 2% κ-carrageenan and locust bean gum, which was close to BP. In the sensory evaluation, Car-2 showed higher scores for sensory preferences than other plant-based patties. Based on our data, incorporating 2% κ-carrageenan could offer a feasible way of crafting plant-based meat analogs due to its potential to enhance texture and flavor. Further studies are required to evaluate the suitability of polysaccharides in various types of plant-based meat analogs.